Chemical decellularization: a promising approach for preparation of extracellular matrix - Hrebikova, Hana; Diaz, Daniel; Mokry, Jaroslav (Biomedical papers, 2015)
Background: A biological scaffold from extracellular matrix can be produced by a variety of decellularization methods whose caveat consists in efficiently eliminating cells from the treated tissue. This scaffold can be used in diverse applications for tissue engineering and organ regeneration. Preservation of the extracellular matrix ultrastructure is highly desirable because of its unique architecture, contained growth factors and decreased immunological response. All of these properties provide attachment sites and adequate environment for cells colonizing this scaffold, reconstituting the decellularized organ. This review briefly describes chemical decellularization methods, evaluation of these protocols and the role of ECM in tissue engineering.Conclusion: Chemical decellularization is an often used method for scaffold preparation and makes possible a well-preserved three dimensional structure of extracellular matrix.
Keywords: chemical decellularization; detergent; extracellular matrix; cell lysis